Presenting to win, updated and expanded edition : the art of telling your story - Weissman, Jerry (Pearson Education, 2024)
Drawing on brand-new case studies, Weissman shows how to identify your key goals and messages before you even open your presentation software; stay focused on what your listeners really care about; and capture your audiences in the first crucial 90 seconds, even if you can't see them. From bullets and graphics to the effective, sparing use of special effects, Weissman covers all the practical mechanics of effective presentation.